Challenges in sustaining the Malay traditional kuih among youth - Hamzah, Humairah; Abdul Karim, Muhammad Shahrim; Othman, Mohiddin; Hamzah, Azimi; Muhammad, Nur Hafizah (International Association of Computer Science and Information Technology (I A C S I T), 2015)
The purpose of the article is to disclose the challenges in sustaining the Malay traditional kuih with differing levels of acceptance among youth in East Coast Peninsular Malaysia. Malay kuih also known as Malay dessert that referring to a product which uses specific raw ingredients; methods; processes; techniques; materials and utensils; and the recipes have been passed down from one generation to other generations. It is part of Malaysian culture, identity and heritage that should be sustained by all generations especially youth. Throughout observation and interviews with youth, age of 18 to 25 years old who are completed their secondary school and basically come from different family backgrounds, the trend of buying pattern among youth towards Malay traditional kuih were influenced by the family, friends and occasions. Six main themes that have been identified are including family, value, knowledge, motivation, way of life and pecuniary. Although all themes were emphasized by youth during the interviews, a closer look revealed that the themes evaluated quite differently based on their age and background. The exhibited divergences are found to be underpinned by different way of life dispositions, which are extremely important and affecting in shaping and influencing values amongst the youth. The results are promising meaningful understanding of the challenges to sustain the Malay traditional kuih among youth, which are reinforced by its complex culture diversities and globalization.